Practices and attitudes about delayed umbilical cord clamping for term infants: a descriptive survey among midwives. (18th August 2022) - Rousseau, Anne; Duron, Marie-Amélie; Letouzey, Mathilde
Abstract: The aim of this study was to assess variations in midwives' practices of cord clamping (early versus delayed) and to identify factors potentially associated with delayed clamping. This was a descriptive cross-sectional survey by self-administered online questionnaire among French midwives working in delivery rooms from March to July 2018. We obtained complete responses from 350 midwives. Only 120 (34.3%) reported always or sometimes performing delayed cord clamping at one minute or more after birth. Delayed cord clamping was significantly associated with midwives' experience (adjusted OR 3.99; 95% confidence interval [CI] 2.10, 7.83 for experience >10 years), maternity unit written protocol (adjusted OR (aOR) 5.17; 95% CI 1.88, 16.00), knowledge of guidelines (aOR 3.33; 95% CI 1.98, 5.71) and neonatal care level 1 (aOR 2.95; 95% CI 1.53, 5.78). Impact Statement: What is already know on this subject? Despite benefits and the safety of delayed cord clamping, many newborns likely had their umbilical cords clamped immediately after delivery as part of routine care or because providers were not convinced of the benefits of delayed clamping. What do the results of this study add? Most of the midwives surveyed did not systematically delay cord clamping. Individual and organisational factors were associated with adherence to guidelines regarding delayed cord clamping. What are the implications of these findings for clinical and/or further research? A protocol should be implemented in every maternity unit with information about the benefits and risks of delayed cord clamping to reduce variations in practice and improve the safety of care.